Analisis Pelaksanaan Discharge Planning - Sri Hariyani; Syukriadi; Riyan Mulfianda (CV. ITTC INDONESIA, 2025)
Discharge planning issues are not only found in Indonesia but also around the world. Global data shows that nurses in several countries do not carry out discharge planning. This results in various negative impacts on patients. This study aims to identify the implementation of discharge planning in Room Tursina 3 of the Dr. Zainoel Abidin General Hospital in Banda Aceh. The research method used is SWOT analysis. The problem found is that the implementation of discharge planning is less than optimal. Results after conducting research on nursing management in Room Tursina 3 of Dr. Zainoel Abidin Hospital, it can be concluded that: the assessment of discharge planning was conducted over two days. The assessment was carried out by collecting data through observation and interviews. After analyzing the data, the diagnosis was that the implementation of discharge planning in Room Tursina 3 of Dr. Zainoel Abidin General Hospital was not optimal. Zainoel Abidin Hospital. Therefore, to address this issue, an intervention involving knowledge dissemination will be implemented. It is hoped that this study can serve as a knowledge resource for Room Tursina 3 at Dr. Zainoel Abidin General Hospital in Banda Aceh regarding the implementation of discharge planning in the inpatient ward at the hospital.